Effect of iron overload and iron deficiency on liver hemojuvelin protein - Krijt, Jan; Frýdlová, Jana; Kukačková, Lenka; Fujikura, Yuzo; Přikryl, Petr; Vokurka, Martin; Nečas, Emanuel (PloS one, 2012)
INTRODUCTION: Hemojuvelin (Hjv) is a key component of the signaling cascade that regulates liver hepcidin (Hamp) expression. The purpose of this study was to determine Hjv protein levels in mice and rats subjected to iron overload and iron deficiency. METHODS: C57BL/6 mice were injected with iron (200 mg/kg); iron deficiency was induced by feeding of an iron-deficient diet, or by repeated phlebotomies. Erythropoietin (EPO)-treated mice were administered recombinant EPO at 50 U/mouse. Wistar rats were injected with iron (1200 mg/kg), or fed an iron-deficient diet. Hjv protein was determined by immunoblotting, liver samples from Hjv-/- mice were used as negative controls. Mouse plasma Hjv content was determined by a commercial ELISA kit. RESULTS: Liver crude membrane fraction from both mice and rats displayed a major Hjv-specific band at 35 kDa, and a weaker band of 20 kDa. In mice, the intensity of these bands was not changed following iron injection, repeated bleeding, low iron diet or EPO administration. No change in liver crude membrane Hjv protein was observed in iron-treated or iron-deficient rats. ELISA assay for mouse plasma Hjv did not show significant difference between Hjv+/+ and Hjv-/- mice. Liver Hamp mRNA, Bmp6 mRNA and Id1 mRNA displayed the expected response to iron overload and iron deficiency. EPO treatment decreased Id1 mRNA, suggesting possible participation of the bone morphogenetic protein pathway in EPO-mediated downregulation of Hamp mRNA. DISCUSSION: Since no differences between Hjv protein levels were found following various experimental manipulations of body iron status, the results indicate that, in vivo, substantial changes in Hamp mRNA can occur without noticeable changes of membrane hemojuvelin content. Therefore, modulation of hemojuvelin protein content apparently does not represent the limiting step in the control of Hamp gene expression.
Keywords: železo; játra; signální transdukce; Hemochromatosis Protein; Membrane Proteins; Iron Overload; Signal Transduction; Iron; erythropoetin; krysa rodu Rattus; Erythropoietin; zvířata; myši; GPI-Linked Proteins; kostní morfogenetické proteiny; myši inbrední C57BL; dietní železo; potkani Wistar; Mice; Bone Morphogenetic Proteins; Liver; Rats, Wistar; Iron, Dietary; Mice, Inbred C57BL; protein hemochromatózy; Rats; membránové proteiny; Animals; přetížení železem; GPI-vázané proteiny; deficit železa; Iron Deficiencies